Simplification of labor registration in Argentina: Achievements and pending issues - Lucas Ronconi; Jorge Colina (Inter-American Development Bank (IDB), 2011)
This paper describes the reforms aimed at simplifying the administrative procedures for labor registration and the payment of social security contributions that were carried out in Argentina in 2005 and 2007. Analysis of the legislation, as well as a survey conducted among accountants, reveals that although the reforms did reduce the administrative burden, the effect was only partial. By using microdata gathered from household surveys conducted quarterly between 2003 and 2009, and the discontinuities according to company size that the legislation engenders, differences-in-differences coefficients have been estimated regarding the impact of the simplification reforms on the labor market. The results indicate that the simplification reforms had a positive, although limited, effect on the labor registration rate (of approximately two percentage points for all workers and nine percentage points for newly-hired workers), but that there was no effect on employment levels. Finally, policy recommendations are put forward aimed at deepening the administrative simplification process and thereby improving its effectiveness as a labor registration promotion mechanism.
hdl:11319/3827
Keywords: J3; J8; O17; 330; simplification; registration; taxes; the labor market; informality; Argentina